Measurement of properties of B(s)(0)s -> mu(+)mu(-) decays and search for B-0 -> mu(+)mu(-) with the CMS experiment - Sirunyan, A. M. (2020)
Results are reported for the B 0s ! + branching fraction and effective lifetime and from a search for the decay B0 ! + . The analysis uses a data sample of proton-proton collisions accumulated by the CMS experiment in 2011, 2012, and 2016, with center-of-mass energies (integrated luminosities) of 7TeV (5 fb), 8TeV (20 fb), and 13TeV (36 fb). The branching fractions are determined by measuring event yields relative to B+ ! J= K+ decays (with J= ! + ), which results in the reduction of many of the systematic uncertainties. The decay B 0s ! + is observed with a significance of 5.6 standard deviations. The branching fraction is measured to be B (B 0s ! + ) = [2:9 0:7(exp) 0:2(frag)] 10, where the first uncertainty combines the experimental statistical and systematic contributions, and the second is due to the uncertainty in the ratio of the B 0s and the B+ fragmentation functions. No significant excess is observed for the decay B0 ! + , and an upper limit of B(B0 ! + ) < 3:6 10 is obtained at 95% confidence level. The B 0s ! + effective lifetime is measured to be + = 1:70 +0:61 ps. These results are consistent with standard model predictions.